Can an increase in the pulmonary vein volume measured by three dimensional computed tomography predict the presence of atrial fibrillation?. Issue 2 (15th February 2019) - Kurata, Masaaki; Asano, Taku; Mori, Hiroyoshi; Mase, Hiroshi; Nagumo, Sakura; Wakatsuki, Daisuke; Shimojima, Hisa; Ebato, Mio; Miyazaki, Akira; Suzuki, Hiroshi
Abstract: Background: Left atrial (LA) dilation is associated with morbidity of atrial fibrillation (AF). However, little is known about pulmonary vein (PV) dilation. Purpose: We investigated the PV volume in the patients with AF. Methods and results: We performed 3dimensional computed tomography (3DCT) in 155 patients and divided them into three groups: 19 patients without AF (non‐AF group, mean age 66 ± 12 years), 50 with paroxysmal AF (PAF group, mean age 67 ± 8 years) and 24 with persistent AF (PeAF group, mean age 64 ± 10 years). The absence of AF was diagnosed in patients with a cardiac implantable electronic device for at least 1 year (mean: 59 ± 37 months). We determined the PV volume as the total volume from the orifice to the first branch of each PV. According to the echocardiographic data, the LA dimension (LAD) and LA volume index (LAVI) were largest in the PeAF group followed by the PAF and non‐AF group. According to the morphometric data obtained on 3D‐CT, the PV volume was similar in PeAF and PAF groups but significantly smaller in the non‐AF group (median value: 24 vs 21 vs 14 mL, respectively). According to the receiver operating characteristic curve analysis, the area under the curve for the PV volume in the presence of AF was 0.80, and the optimum cut‐off value was 17 mL (sensitivity 74%, specificity 80%). Conclusion: The PV volume might be useful for predicting the presence of AF before increases in the LAD and LAVI on echocardiography.